2022
DOI: 10.1159/000525629
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Challenges in Cannabis Drug Delivery Systems: Where Are We?

Abstract: Cannabis and its natural derivatives have emerged as promising therapeutics for multiple pathological and nonpathological medical conditions. For example, cannabinoids, the most popular and biologically active chemicals in cannabis, aid in many clinical ailments, including pain, inflammation, epilepsy, sleep disturbances or insomnia, multiple sclerosis, anorexia, schizophrenia, neurodegenerative diseases, anti­nausea, and most importantly, cancer. Despite the comprehensive benefits, certain aspects of cannabis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 118 publications
(197 reference statements)
0
25
0
Order By: Relevance
“…Therefore, rigorous pharmacokinetic studies in animals and humans are essential to optimise dosing strategies to understand α -humuleneʼs therapeutic potential 68 . Strategies to enhance α -humuleneʼs bioavailability, such as formulations that improve solubility and stability, could significantly enhance its clinical utility 69 . There is one pilot study currently underway seeking to explore the effects of α -humulene on stress when combined with forest bathing, for which the results will be eagerly awaited 70 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, rigorous pharmacokinetic studies in animals and humans are essential to optimise dosing strategies to understand α -humuleneʼs therapeutic potential 68 . Strategies to enhance α -humuleneʼs bioavailability, such as formulations that improve solubility and stability, could significantly enhance its clinical utility 69 . There is one pilot study currently underway seeking to explore the effects of α -humulene on stress when combined with forest bathing, for which the results will be eagerly awaited 70 .…”
Section: Discussionmentioning
confidence: 99%
“…The need to study drug delivery systems aims to maximize therapeutic efficacy or minimize side effects by impacting the absorption, distribution, metabolism, and elimination of a drug compound [ 123 ]. The elaboration of an edible delivery system for active bio compounds is challenging due to the differences in solubility, bioavailability, and potential for novel food and pharmaceutical applications.…”
Section: Discussionmentioning
confidence: 99%
“…Low dosages of ∆9-THC likely produce conditioned rewarding effects, whereas higher levels produce conditioned aversive effects [ 110 ]. Research on the endocannabinoid system’s control of food intake found that high dosages of cannabinoids showed orexigenic (appetite stimulant) effects, whereas low doses had anorexigenic (loss of appetite) effects [ 111 ].…”
Section: Individuality Of Responsementioning
confidence: 99%